Academic Skills in High-Functioning and Low-Functioning Chinese Children with Autism - Layton, Thomas; Hao, Grace (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
Early academic skills among Chinese speaking children with ASD were compared to age matched peers who were typically developing and with intellectual disabilities. In general, children with ASD do perform less well on reading comprehension, writing, and math skills. The purpose of the current study was to gather preliminary data on the early academic skills of Chinese children with ASD. The findings indicated that HFA and LFA had less difficulty in acquiring beginning basic-academic skills, but had more difficulty in acquiring advanced academic skills compared to their peers. Yet, the two groups of Chinese students with HFA and LFA performed remarkably alike across the academic skills.